The impact of repeated ad exposure on spillover from low fit extensions to a global brand. Issue 2 (11th April 2016) - Lane, Vicki R.; Fastoso, Fernando
Abstract : Purpose: – Previous research warns against low-fit extensions as prone to causing negative spillover and, through it, harming the parent brand equity. Using the theory of schema-triggered affect and the link formation hypothesis, the purpose of this paper is to develop and tests predictions as to how negative spillover from low-fit extensions can be actively managed through repeated ad exposure. Design/methodology/approach: – A controlled experiment assesses the response of US consumers to the Dutch Heineken brand, a top 100 global brand, following sequential and repeated exposure to print ads depicting extensions for either Heineken wheat beer (i.e. a high-fit extension) or Heineken pretzels (i.e. a low-fit extension). Analytical methods include multiple regression, ANOVA, and t -tests. Findings: – The findings show that repeated ad exposure has a positive moderating effect on the magnitude of spillover from extension to brand. Second, the findings also show that repeated ad exposure changes the valence of spillover from low-fit extension to brand from negative to positive. In combination, the findings suggest that low-fit brand extensions can, when carefully managed, be a viable strategic option for market growth that is especially relevant for global brands. Research limitations/implications: – This research shows that repeated ad exposure can change the valence of spillover from low-fit extensions to the parent brand from negative to positive. Future research should extend the work by considering other brands and alternative tools that managers can use to make low-fit extensions a viable strategic choice. Practical implications: – This study finds, in contrast to previous research, that managers should indeed consider low-fit brand extensions as a viable strategic option for brand growth. This is possible because the findings show that repeated ad exposure can be used to control potential negative spillover from a low-fit extension to parent brand. This conclusion is particularly relevant for global brands, i.e. brands for which the opportunity costs of limiting global expansion and the financial investment necessary to establish a new brand with global appeal are substantial. Originality/value: – This paper differs from other spillover studies by manipulating repeated ad exposure, a mechanism which the authors theoretically link to spillover and which managers can also directly influence. In doing so, this paper offers a theoretical explanation and an empirical test of how negative spillover from low-fit extensions can be managed.